THE EFFECT OF ADVERTISING AND PERCEPTION OF QUALITY ON PURCHASE DECISIONS FOR SKINTIFIC CUSHION IN TIKTOK SHOP - Armanda Fitri Aulia Br Manurung; Mutiara Dwinata; Dedy Dwi Arseto; Mhd Sofian (CV. Radja Publika, 2025)
This study aims to analyze the impact of advertising and perceived quality on purchasing decisions for Cushion Skintific products on TikTok Shop. In the context of the Indonesian market, which is a potential market for the beauty industry, Skintific products, which originate from Canada and are manufactured in China, have succeeded in attracting consumers' attention thanks to the latest skincare technology innovations. The method used in this study is quantitative, with data collection through questionnaires distributed to 100 respondents who are users of Cushion Skintific products. The results of the analysis show that effective advertising and high perceived quality have a significant contribution to purchasing decisions. Sales data recorded a significant increase, especially in December 2024, where sales reached 86,602 pcs. These findings emphasize the importance of creative promotional strategies and positive perceptions of product quality in influencing consumer purchasing decisions, especially among the younger generation who are active on social media. This study provides valuable insights for marketers to continue to improve product quality and advertising intensity in order to maintain attractiveness in a competitive market.